Investigating the relationships between load and recovery in women`s field hockey - Female Athletes in Motion (FAiM) study - Vescovi, J. D.; Klas, A.; Mandic, I. (International Journal of Performance Analysis in Sport, 2019)
This study examined the relationships between internal and external load metrics with subjective wellness-recovery indices in female field hockey players. Specifically, to evaluate 1) morning wellness-recovery with the current day loads (same-day analysis), and 2) the current day loads with wellness-recovery the following morning (next-day analysis). Objective (total distance and training impulse) and subjective (session RPE) load metrics as well as subjective indices of recovery and wellness were monitored daily with a women`s U21 field hockey team (n = 16) during a 16-day European tour (8 matches and 7 training sessions). Linear-mixed models were used to quantify the relationship between load and wellness-recovery metrics. A unit rise in wellness was associated with a 37.8 m increase in total distance for the sessions that day (p = .038); otherwise there were no correlations observed between load and wellness-recovery metrics for same-day and next-day analysis. There was substantial intra-individual variation among players for these relationships. Over the course of a typical field hockey event player responses were not evident at a group-level. Therefore, it is important for coaches and support staff to monitor individual changes in the loads experienced along with wellness-recovery patterns. Subsequent adjustments could have implications regarding performance, fatigue management, and athlete well-being.